THE IMPACT OF IMPRESSION MANAGEMENT ON TEMPORARY IMAGE RISK IN PRINCIPAL LEADERSHIP - Hasri, Salfen; Dinata, Yuriyan; Rohaini, Yespi; Sohiron, Sohiron (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: School principals play a strategic role in building a positive perception within an educational institution, which has an impact on improving trust, motivation, and organizational performance. One often-used strategy is impression management, which manages communication, leadership symbols, and interpersonal interactions. However, if not managed proportionately, this strategy can pose risks in the form of temporary imagery, negative biases, and manipulative perceptions, damage weak leadership credibility, and damage internal organizational relationships. Purpose of the Study: This study aims to analyze the role of impression management by school principals in building positive perceptions and identify risks arising from disproportionate and ineffective implementation. Methods: This study uses a library research approach by reviewing literature on impression management, perception, and leadership. The data was analyzed using content analysis to identify themes, patterns, and relationships between concepts. The analysis was also carried out using Karl Popper's falsification principle to test the dentist concept concepts' validity and avoid bias, the dentist concept concepts' validity and avoid bias. The mental idol Francis Bacon identifies and minimizes subjective bias in data interpretation. Results: The study shows that wise impression management can increase trust, motivation, and organizational performance. However, if not managed proportionally, it can create manipulative perceptions and reduce the trust of organizational members. This research makes theoretical and practical contributions to helping school principals manage impression management effectively to achieve more credible and sustainable leadership.